Comparisons of benthic associated fauna assemblages in seagrass meadows across conservation and non-conservation areas in Bali and Lombok, Indonesia - Atmaja, Putu Satya Pratama; Laharjana, I Ketut Aditya Krisna; Suardana, A. A. Md. Ananda Putra; Van Keulen, Mike (Marine Science Department Diponegoro University, 2024)
Benthic ecosystem has been widely considered as an important feature of seagrass associated fauna, and its function as a grazer and linkage between primary producers and higher trophic level is well known. Though the importance of benthic fauna in seagrass ecosystems has been indicated in many studies, its biodiversity in spatial scale has often been poorly studied. This study aimed at examining the assemblages and diversity of benthic associated fauna in conservation areas (CA) and non-conservation areas (NCA) across the seagrass meadows in Bali and Lombok. This study found that the assemblages and diversity of benthic fauna greatly varied between the meadows. A total of 430 individuals associated to benthic fauna from 24 species were identified in Bali and Lombok. Of these, Gastropods were the highest class of taxa recorded in this study, followed by Bivalvia, Echinodermata, Decapoda, and Amphipoda. Permutation multivariate analysis of variance (PERMANOVA) revealed a significantly different benthic fauna diversity between sites. Non-metric Multidimensional Scaling (nMDS) and Bray–Curtis analysis showed a clear distinction of benthic fauna assemblages between CA and NCA, both in Bali and Lombok. These results indicated that from spatial perspective, different characteristics of seagrass meadows may represent different biodiversity of associated fauna. These differences might be driven by different anthropogenic pressure and variation of substrates among the meadows which may affect the composition of the benthic fauna ecosystems. The implication of this study was to providing baseline data on guiding the appropriate approach and strategies for management and conservations of seagrass ecosystems.